Headache Disability Questionnaire: cross-cultural adaptation and validation of the Turkish version - Halime Arikan (BMC Neurology)
Abstract Background The Headache Disability Questionnaire (HDQ) evaluates pain intensity, daily activities, work/school disruptions, and the impact on recreational activities. It was aimed to translate the HDQ into Turkish and evaluate its reliability and validity. Methods This study included 130 participants, consisting of 105 females and 25 males. The original HDQ was translated into Turkish language using Beaton guidelines. Reliability was assessed using internal consistency and Intraclass Correlation Coefficient. Exploratory (EFA) and Confirmatory Factor Analysis (CFA) were conducted to evaluate the structural validity. For convergent validity, the Turkish version of the HDQ, along with the Headache Impact Test-6 (HIT-6) and Migraine Disability Assessment Scale (MIDAS), was administered to individuals with headaches. The HDQ was retested one week later to assess its reliability. Results The Turkish version of the HDQ demonstrated good reliability, with ICC and Cronbach’s α values of 0.842 and 0.914, respectively. Standard error measurement (SEM) and Minimal Detectable Change (MDC) values were 5.89 and 16.33 units. Bland-Altman plots confirmed a high level of agreement between initial and retest scores EFA revealed a two-factor structure, clustering items into Factor 1 (items 1, 2, 5, 7, and 9) and Factor 2 (items 3, 4, 6, and 8), which was subsequently confirmed by CFA. Convergent validity was confirmed through good correlations with HIT-6, and MIDAS. No ceiling or floor effects were observed. Conclusions The study demonstrates that the Turkish version of the HDQ is a valid and reliable instrument for evaluating the effect of headaches on daily living, exhibiting strong internal consistency and test-retest reliability, making it suitable for both clinical practice and research purposes. Trial registration Trial registration date is January 30, 2021 (NCT04736654). Clinical trials registration number NCT04736654.